(untitled) (Journal of Fiber Bioengineering and Informatics, 2018)
For firefighter protective clothing, thermal protective performance is of primary importance. In this regard, the effects of thermal barrier construction on the level of thermal protection were investigated. In this study, needle punched nonwovens of varying thicknesses for application as thermal barrier were prepared from 100% meta-aramid, 100% wool, and 90% meta-aramid/10% para-aramid fibers. The effect of the number of layers in multilayer thermal barriers prepared from these nonwovens and the effect of spacers on the thermal protective performance were examined. The possibility of incorporation of aerogels into the thermal barrier to enhance the protective performance was examined. The needle punched nonwovens were padded with 5 wt% aerogels dispersion in acetone. The differences in thermal protective performance of nonwovens were evaluated by heat transmission on exposure to flame, heat transmission on exposure to radiant heat and heat transmission on exposure to both flame and radiant heat methods. Multi layer constructions with spacers and nonwovens treated with aerogels exhibited higher thermal protective performance.